Four year efficacy of prophylactic human papillomavirus quadrivalent vaccine against low grade cervical, vulvar, and vaginal intraepithelial neoplasia and anogenital warts: randomised controlled trial (2010)
Objectives: To evaluate the prophylactic efficacy of the human papillomavirus (HPV) quadrivalent vaccine in preventing low grade cervical, vulvar, and vaginal intraepithelial neoplasias and anogenital warts (condyloma acuminata). Design: Data from two international, double blind, placebo controlled, randomised efficacy trials of quadrivalent HPV vaccine (protocol 013 (FUTURE I) and protocol 015 (FUTURE II)). The trials were to be 4 years in length, and the results reported are from final study data of 42 months' follow-up. Setting: Primary care centres and university or hospital associated health centres in 24 countries and territories around the world. Participants: 17 622 women aged 16-26 years enrolled between December 2001 and May 2003. Major exclusion criteria were lifetime number of sexual partners (>4), history of abnormal cervical smear test results, and pregnancy. Intervention: Three doses of quadrivalent HPV vaccine (for serotypes 6, 11, 16, and 18) or placebo at day 1, month 2, and month 6. Main outcome measures: Vaccine efficacy against cervical, vulvar, and vaginal intraepithelial neoplasia grade I and condyloma in a per protocol susceptible population that included subjects who received all three vaccine doses, tested negative for the relevant vaccine HPV types at day 1 and remained negative through month 7, and had no major protocol violations. Intention to treat, generally HPV naive, and unrestricted susceptible populations were also studied. Results: In the per protocol susceptible population, vaccine efficacy against lesions related to the HPV types in the vaccine was 96% for cervical intraepithelial neoplasia grade I (95% confidence interval 91% to 98%), 100% for both vulvar and vaginal intraepithelial neoplasia grade I (95% CIs 74% to 100%, 64% to 100% respectively), and 99% for condyloma (96% to 100%). Vaccine efficacy against any lesion (regardless of HPV type) in the generally naive population was 30% (17% to 41%), 75% (22% to 94%), and 48% (10% to 71%) for cervical, vulvar, and vaginal intraepithelial neoplasia grade I, respectively, and 83% (74% to 89%) for condyloma. Conclusions: Quadrivalent HPV vaccine provided sustained protection against low grade lesions attributable to vaccine HPV types (6, 11, 16, and 18) and a substantial reduction in the burden of these diseases through 42 months of follow-up. Trial registrations: NCT00092521 and NCT00092534.